FINANCIAL LITERACY AND ENTREPRENEURSHIP-BUSINESS STARTUP FOR EFFECTIVE POST-RETIREMENT LIFE MANAGEMENT AMONG PRE-RETIREES IN UNIVERSITIES IN EDO STATE, NIGERIA - Oriazowanlan, Obose Angela (APPS Publications, 2023)
The role of entrepreneurship to prevent poverty and mitigate other post-retirement challenges has been acknowledged to be crucial for effective post-retirement life management but financial constraints could constitute bane to pre-retirees’ entrepreneurial intentions. Therefore, the study determined the financial knowledge that could spur their intentions and readiness for business start that could enable them surmount post-retirement life challenges. Two research questions guided the study. The descriptive survey research design was adopted and the population comprised all the pre-retirees in universities in Edo State. 250 respondents were randomly selected using the simple random sampling technique from three purposive selected universities. Primary data were gathered through the use of structured questionnaire which was validated and tested to have reliability coefficient value of 0.84. The descriptive statistics of mean and standard deviation were used to answer the research questions and test the respondents’ homogeneity. The findings revealed among others that the respondents perceived the benefits of entrepreneurship-business startup to ensure their effective post-retirement life management but intend to rely totally on their retirement savings benefits with the Contributory Pension Scheme (CPS) for business startup. Based on the findings it was recommended among others that pre-retirees should make contingency savings plan and that the employers and government should provide them financial education in order to acquaint them with relevant financial knowledge to access other forms of business financing such as loans, bank overdraft, angel investors, venture capital and government grants among others prior to final disengagement.